Division of paid and care work between parents: Reality often differs greatly from the ideals - Ludovica Gambaro; Annica Gehlen; C. Katharina Spieß; Katharina Wrohlich; Elena Ziege (DIW Weekly Report, 2024)
On average, mothers and fathers in Germany divide paid work and care work very unequally. Mothers often only work part time, which results in further gender inequalities in the labor market. A current analysis of data from the German Family Demography Panel Study (FReDA) shows that the population's attitudes toward the ideal division of work between couples with children under 12 are considerably more egalitarian than the actual behavior of couples with young children of different ages. This discrepancy is due in part to the financial incentives of the German tax and transfer system for married couples, which arise from the interplay between income splitting (Ehegattensplitting) and the tax treatment of mini-jobs. In addition, childcare infrastructure is insufficient and a very high gender pay gap persists in Germany. If policymakers want to dismantle inequalities in the labor market, the tax and transfer system must be modernized and childcare options expanded to make a more equal division of paid work and care work between parents more appealing.
Keywords: D13; J16; J22; 330; family labor supply; gender gaps; social norms; tax and transfer system; work incentives